Advancing food-drying techniques: design and performance of a multi-layered drying rack - Ab Aziz, I. F.; Che Man, H.; Shamsudin, R.; Ismail, M. F.S.; Bathumaly, S. (Rynnye Lyan Resources, 2025)
The drying process is crucial in food processing and preservation, impacting various biomaterials, including fruits, vegetables, grains, fish, and meat. This study introduces the Multi-Layered Aqua Mate Dryer (MAMADry), a novel vertical multi-layered greenhouse system designed to optimize the drying process. The closed polycarbonate structure of MAMADry offers protection against external contaminants, while its efficient design reduces drying times significantly compared to traditional sun-drying methods. The study demonstrated MAMADry's effectiveness in achieving faster, controlled, and uniform drying within only 72 hrs of drying using Water Hyacinth (13.1% moisture content wet basis) and Giant Salvinia (15.1% moisture content wet basis) as test samples compared to sun drying (144 hrs of drying). MAMADry presented a promising alternative for small-scale farmers in search of cost-effective drying solutions that offer rapid processing times, safeguard against environmental factors, ensure food safety, and minimize space requirements. This innovative technology had the potential to facilitate the efficient drying of diverse agricultural and seafood products.